Hit to lead - Rafferty, Michael (Henry Stewart Talks, 2013)
Defining hit-to-lead as the first phase of medicinal chemistry, Selection of hits to begin a hit to lead campaign, Overview of processes and technologies, Risk factors that influence or determine success